Application of integrated traditional Chinese and Western medicine nursing in the treatment of chronic heart failure in the elderly (中西医结合特色护理在老年慢性心力衰竭治疗中的应用) - ZHENG Chao (郑超); LI Ning (李宁); CAO Hongjing (曹红京) (Journal of International Translational Medicine Limited, 2024)
To　evaluate the integrated traditional Chinese and western medicine nursing interventions in the treatment of chronic heart failure in the elderly. The hospital had established an integrated traditional Chinese and western medicine nursing model based onmulti-disciplinary team. Based on the treatment of acute exacerbation of chronic heart failure, comprehensive nursing interventions of integrated traditional Chinese and Western medicine were carried out including Traditional Chinese Medicine treatment by syndrome differentiation, Traditional Chinese Medicine characteristic nursing, nursing of insomnia, dietary nursing, Traditional Chinese Medicine enema, volume monitoring, skin care, extended care. (探讨适合我国国情的老年慢性心力衰竭的中西医结合治疗模式和特色护理模式。医院在老年慢性心力衰竭治疗中形成了以多学科合作为基础的中西医结合特色护理模式, 包括慢性心衰急性期治疗与护理、中医辨证施治、中医护理、失眠护理、叙事护理、饮食护理、中药灌肠、出入量监测、皮肤护理、延续性护理等。)